DECONSTRUCTING THE STEREOTYPE OF MADURA: A SOCIAL, CULTURAL, AND RELIGIOUS STUDY - Suryanto, Totok Agus; Ruslan, Ruslan Ruslan; Argantara, Zaid Raya (Universitas Al-Amien Prenduan, 2025)
This research aims to deconstructively describe the five faces of the central concept of maduraness, which has been stereotyped by many parties as full of subjective bias, so that such construction at its peak brings a negative stigma to the social reality of maduraness. For this reason, aligning academic understanding is necessary to prevent the stereotype from spreading like an uncontrollable virus. This research uses a qualitative-phenomenological method approach by conducting in-depth interviews with figures with purposive sampling techniques, as well as a serious literature review, so that many stereotypes of Madurese people are found, including: carok as a tradition, culture and identity of Madura, possessiveness of women, barbarism of cattle races and hyper egoism of Madurese people.